2013
DOI: 10.3389/fnmol.2013.00019
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder causes, mechanisms, and treatments: focus on neuronal synapses

Abstract: Autism spectrum disorder (ASD) is a group of developmental disabilities characterized by impairments in social interaction and communication and restricted and repetitive interests/behaviors. Advances in human genomics have identified a large number of genetic variations associated with ASD. These associations are being rapidly verified by a growing number of studies using a variety of approaches, including mouse genetics. These studies have also identified key mechanisms underlying the pathogenesis of ASD, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(151 citation statements)
references
References 328 publications
1
137
0
5
Order By: Relevance
“…ASD is characterized by deficits in social interaction and communication, restricted interests, and repetitive behaviors, and the aberrant development and function of synapses is known to be involved in its pathogenesis [62] .…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…ASD is characterized by deficits in social interaction and communication, restricted interests, and repetitive behaviors, and the aberrant development and function of synapses is known to be involved in its pathogenesis [62] .…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…While previous studies have demonstrated that miR-137 regulates dendritic development both in vitro and in vivo in adult granule neurons 7,9 , the function of miR-137 in the presynaptic compartment remains unexplored. It is crucial to elucidate the functional consequences of psychiatric-associated gene variants as cognitive and synaptic dysfunctions are phenotypes common to schizophrenia and autism spectrum disorders 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although many approaches have attempted to identify "molecular pathways" implicated in ASDs to unify disparate genes, these data have not converged to provide conclusive and well-replicated evidence. How these mutations lead to ASD phenotypes is poorly understood (for review see [91,92]). Hence, most cases still remain unknown, but potentially, including additional less penetrant rare variants or complex mechanisms, such as gene-gene interaction or gene-environment interaction.…”
Section: Molecular Pathways Asd: "Developmental Synaptopathies"mentioning
confidence: 99%